2021
DOI: 10.3389/fcell.2021.691676
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Risk Model Based on Lipid Metabolism-Associated Genes Predicts Prognosis and Indicates Immune Microenvironment in Breast Cancer

Abstract: BackgroundBreast cancer (BRCA) is the most common tumor in women, and lipid metabolism involvement has been demonstrated in its tumorigenesis and development. However, the role of lipid metabolism-associated genes (LMAGs) in the immune microenvironment and prognosis of BRCA remains unclear.MethodsA total of 1076 patients with BRCA were extracted from The Cancer Genome Atlas database and randomly assigned to the training cohort (n = 760) or validation cohort (n = 316). Kaplan–Meier analysis was used to assess d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 63 publications
3
13
0
Order By: Relevance
“…Compared to cluster 2, the prognosis of the patients in cluster 1 was poor, accompanied by a high abundance of immunosuppressive cells and a general increase in the expression of immune checkpoints, indicating an immunosuppressive microenvironment. This is consistent with findings regarding other malignancies [ 6 , 13 , 14 , 21 ]. As the consensus clustering was based on a MAG expression matrix, we inferred that the expression of MAGs was related to the prognosis and immunosuppressive microenvironment of DLBCL patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Compared to cluster 2, the prognosis of the patients in cluster 1 was poor, accompanied by a high abundance of immunosuppressive cells and a general increase in the expression of immune checkpoints, indicating an immunosuppressive microenvironment. This is consistent with findings regarding other malignancies [ 6 , 13 , 14 , 21 ]. As the consensus clustering was based on a MAG expression matrix, we inferred that the expression of MAGs was related to the prognosis and immunosuppressive microenvironment of DLBCL patients.…”
Section: Discussionsupporting
confidence: 93%
“…It is necessary for us to develop new strategies to identify risk among DLBCL patients more reliably, so as to personalize treatment strategies. Recent studies have shown that risk models based on multi-gene expression are a reliable choice [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PLA2G2D was identified as one of the high-risk genes for colorectal and rectum adenocarcinoma that were negatively correlated with patient survival. However, PLA2G2D expression was also found to be positively correlated with immune infiltration and better prognosis in head and neck squamous cell carcinoma and breast cancer in human (49,50), which is consistent with our current findings in CSCC. The opposite effects of PLA2G2D in different cancer types may result from the distinct microenvironments and different downstream lipid mediators presented in each cancer type, which in turn result in either an elevated or dampened inflammatory responses, thereby leading to the distinct clinical outcomes reported in these investigations (48).…”
Section: Discussionsupporting
confidence: 92%
“…demonstrated that piRNA-30473, which promotes DLBCL progression by regulating m6A RNA methylation in DLBCL, can improve the prognostic stratification and therapeutic approach ( 31 ). With the development of next-generation sequencing, many prognostic cancer models have been established in recent years ( 32 34 ) based on public transcriptomic databases such as the GEO and TCGA datasets.…”
Section: Discussionmentioning
confidence: 99%